PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. INTAN GIRI ABADI JAKARTA SELATAN - Dwi Chahyani, Shella; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of leadership style and organizational culture on employee performance at PT Intan Giri Abadi South Jakarta both partially and simultaneously. The research method used is quantitative which is associative in nature. The sampling technique used a saturated sample technique totaling 60 employees. Data collection techniques through primary and secondary data. The results showed that Leadership Style (X₁) and Organizational Culture (X₂) had an effect on employee performance with a regression equation of Y = 1.138 + 0.550 X₁ + 0.546 X₂ with a coefficient of determination of 80.9% The results of hypothesis testing partially affect leadership style on employee performance with the test results t count> t table or 3.097> 1.67155 then Ho₁ rejected Ha₁ accepted. Partially, organizational culture affects employee performance with the test results of t count> t table or 4,070> 1,67155, so Ho₂ is rejected and Ha₂ is accepted. The results of hypothesis testing simultaneously the value of F count> F table or 121,007> 3,159 then Ho₃ is rejected and Ha₃ is accepted. It can be concluded that the results of the study show that leadership style and organizational culture affect employee performance at PT. Intan Giri Abadi South Jakarta.